Biodiversity and Present Status of Phytoplankton in Mumbri Creek of South Konkan, Maharashtra. - Dekate HM; Baviskar RN (International Journal of Life Sciences, 2016)
The present investigation was carried out in Mumbri Creek of Sindhudurg district (Lat. 16º 21’ N. Long. 73º 25’ E). The main aim of this work is to find out the productivity of the said creek. The phytoplanktons are the surface living energy trapping tiny green organisms. They play a significant role in food chain and web. It is believed that 80% of oxygen that we breathe comes from these tiny plant bodies. Bacillariophyceae, cyanobacteria, dinoflagellates, silicoflagellates were predominating. The primary productivity of an ecosystem is directly correlated with the density of phytoplankton. The physico-chemical parameters of the creek are directly correlated with their formation. The present investigation was done in July 2015-16.